Cervicare™ induces apoptosis in HeLa and CaSki cells through ROS production and loss of mitochondrial membrane potential. Issue 29 (7th March 2016) - Amini, Neda; Abdul Majid, Fadzilah Adibah; Marvibaigi, Mohsen; Supriyanto, Eko; Jaganathan, Saravana Kumar; Tet Soon, Wong; Nasiri, Rozita; Hamzehalipour, Javad
Abstract : The effect of the ethanol and aqueous extracts of Cervicare™, a poly-herbal preparation comprised of the combination of 6 plants, on cell proliferation and apoptosis using cervical cancer HeLa and CaSki cells was investigated for the first time in the present study. Abstract : Cervicare™ is a poly-herbal preparation comprised of a combination of 6 plants; most have demonstrated antimicrobial and anticancer properties in preclinical studies. The effect of the ethanol and aqueous extracts of Cervicare™ on cell proliferation and apoptosis using cervical cancer HeLa and CaSki cells was investigated for the first time in the present study. MTT assay results showed that Cervicare™ extracts exerted time- and dose-dependent inhibition of cell viability. The hallmark properties of apoptosis like cell shrinkage and cytoplasmic condensation were observed using an inverted phase contrast microscope, ethidium bromide/acridine orange and Hoechst 33342/propidium iodide fluorescent staining methods. Furthermore, our results demonstrated that Cervicare™ extracts induced apoptosis in HeLa and CaSki cells by ROS generation and mitochondrial depolarization in a concentration dependent manner. The results showed that Cervicare™ extracts were capable of suppressing cell migration and inhibiting colony formation in a dose-dependent manner. Moreover, western blot analysis demonstrated the involvement of a mitochondria-dependent apoptosis pathway in the apoptosis inducing activity of Cervicare™ ethanol extract in HeLa cells. GC-MS analysis of the ethanolic extract afforded the identification of 40 substances, showing that it was primarily composed of anti-cancerous compounds such as xanthorrhizol (60.40%), octacosane (9.93%) and squalene (1.24%). Together, these results point out the Cervicare™ mediated inhibition of HeLa cell growth via induction of apoptosis and that it may be a potential anticancer agent which deserves further investigation.